Regulatory stress testing and bank performance - Lukas Ahnert; Pascal Vogt; Volker Vonhoff; Florian Weigert (University of Cologne, Centre for Financial Research (CFR), 2020)
This paper investigates the impact of stress testing results on bank's equity and CDS performance using a large sample of twelve tests from the US CCAR and the European EBA regimes in the time period from 2010 to 2018. We find that passing banks experience positive abnormal equity returns and tighter CDS spreads, while failing banks show strong drops in equity prices and widening CDS spreads. We also document strong market reactions at the announcement date of the stress tests. Although the institutional designs between US and European stress tests differ, we generally observe similar capital market consequences for both regimes. We complement existing studies by investigating the predictability of stress test outcomes and evaluating strategic options for affected banks and investors.
Keywords: G00; G21; G28; 330; Banks; Stress Testing; Equity Performance; CDS Performance